1996
DOI: 10.1017/s0890037x00040987
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control by Spring Cover Crops and Imazethapyr in No-till Southern Pea (Vigna unguiculata)

Abstract: Studies were conducted at the Vegetable Substation in Kibler, AR, in 1992 and 1993, in the same plots, to evaluate weed suppression by spring-seeded cover crops and to determine the effects of cover crop and imazethapyr on no-till southern pea. A plot without cover, conventionally tilled before planting southern pea, served as control. Weed control treatments, applied as subplots in each cover crop, included a weedy check, handweeded check, and half and full rates of imazethapyr (0.035 and 0.07 kg/ha) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
2
9
0
2
Order By: Relevance
“…Instead, they provide species‐specific, partial weed suppression during early season growth of summer crops (Liebl et al . 1992; Ateh & Doll 1996; Burgos & Talbert 1996; Teasdale 1996; Yenish et al . 1996; Reddy 2001b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they provide species‐specific, partial weed suppression during early season growth of summer crops (Liebl et al . 1992; Ateh & Doll 1996; Burgos & Talbert 1996; Teasdale 1996; Yenish et al . 1996; Reddy 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…1999), soybean ( Glycine max L.) (Ateh & Doll 1996), and southern pea ( Vigna unguiculata (L.) Walp.) (Burgos & Talbert 1996). Rye is considered an important cover crop because of its potential to withstand harsh winter conditions and produce abundant biomass that can suppress weed germination and the emergence of certain weed species.…”
Section: Introductionmentioning
confidence: 99%
“…Weed suppression may also occur from allelopathic compound that are released from cover crop residues Shilling et al, 1985;. Burgos and Talbert (1996) reported that the cover crops Italian rygrass (Lolium perenne L.), oat (Avena sativa), and sorghum-sudangrass (Sorghum bicolor-Sorghum bicolor var. Sudanese) reduced Palmer amaranth populations between 32 and 59% for 9 wk after crop planting, in the absence of herbicides.…”
mentioning
confidence: 99%
“…우리나라에서도 친환경농업의 실천을 위해 농가현 장에 적용할 수 있는 화학비료 대체기술로서 자운영, 청보 리, 트리티케일 등의 녹비작물이 다양하게 연구되고 있다 (Lee et al, 2009;Park et al, 2009). 그러나 논 토양에 투입된 녹비는 혐기적인 조건에서 미생물에 의해 초기에 다 량으로 분해되므로 녹비의 C/N율과 산소부족으로 인한 토 양 생태계의 심각한 변동을 가져올 수 있다 (Burgos and Talbert, 1996;Teasdale and Daughtry, 1993). 그러나 이 러한 문제점에도 불구하고 투입된 녹비가 벼 생육초기에 토 양 미생물의 다양성에 미치는 영향을 검토한 연구는 거의 없다.…”
Section: 서 언unclassified